Immunity to cytomegalovirus in early life - Huygens, Ariane; Dauby, Nicolas; Vermijlen, David; Marchant, Arnaud (Frontiers in Immunology, 2014)
Cytomegalovirus (CMV) is the most common congenital infection and is the leading non-genetic cause of neurological defects. CMV infection in early life is also associated with intense and prolonged viral excretion, indicating limited control of viral replication. This review summarizes our current understanding of the innate and adaptive immune responses to CMV infection during fetal life and infancy. It illustrates the fact that studies of congenital CMV infection have provided a proof of principle that the human fetus can develop anti-viral innate and adaptive immune responses, indicating that such responses should be inducible by vaccination in early life. The review also emphasizes the fact that our understanding of the mechanisms involved in symptomatic congenital CMV infection remains limited.